Expectations and perceived value of customer satisfaction towards counter service provided by Employee’s Provident Fund (EPF) Muar / Nurul Hanim Abdul Malek - Abdul Malek, Nurul Hanim (2009)
Although service quality and customer satisfaction is related concepts, they are not exactly the same things. The customer’s perception about service quality is based on long term, cognitive evaluations of EPF’s service delivery, where as customer satisfaction is a short-term emotional reaction to specific service experience. Before EPF’s customer purchase a service, they have an expectation about the service quality that is based on individual needs, past experience, worth of mouth recommendation and also a EPF’s advertising. This research focus on the customer satisfaction toward the service quality between expectations and perceived value provided by EPF Muar. From finding, the EPF provide with the useful information to maintain and upgrade its service quality in giving a maximum satisfaction towards their customers. A set of 30 questionnaires were distributed to the respondents who are currently users of EPF services. The questionnaire was designed to capture recalled expectations after visitation and perceptions in the post-experience phase.This survey is conducted at EPF Muar counter service at Jalan Petri, 84000 Muar, Johor and about 43 questions were asked to gather accurate information. All the information is analyzed and majority of the respondents are satisfied towards counter service provided by EPF Muar. They also agree that the service quality provided matched with their expectation. Even though majority of the respondents have an excellent perception towards the service provided by EPF Muar but there is still a needed for EPF to make an improvement in their service from time to time.